Pengaruh Edukasi Personal Hygiene terhadap Pencegahan Infeksi Saluran Kemih pada Lansia dengan Kateter di Ruang Babussalam Rumah Sakit Islam Sultan Hadlirin Jepara - Saiful Anas; Ratna; Feri Catur Yuliani (Prodi Keperawatan Purwokerto, 2025)
Background: Hospitals are places where people seek medical assistance for their health problems. In practice, there are often irregularities and complaints in service delivery that reflect patient dissatisfaction with the services provided. Increasing patient satisfaction requires effective communication to explain each stage of care. Objective: To determine the relationship between nurses' therapeutic communication and patient satisfaction in non-haemorrhagic stroke patients at the Neurology. Methods: The study was a correlational design. The study was conducted at the Neurology Clinic of Prof. Dr. Ir. Prof. Hospital. The samples consisted of 64 respondents who were selected through purposive sampling. Univariate analysis was performed using a frequency distribution test, while bivariate analysis used a chi-square test and Spearman rank correlation test. Results: The results showed there was a positive relationship between nurse-therapeutic communication and patient satisfaction in non-haemorrhagic stroke patients (p=0.000). Conclusion: This study found a significant relationship between nurses' therapeutic communication and patient satisfaction in non-haemorrhagic stroke patients To increase patient satisfaction, nurses are expected to improve therapeutic communication in their services.